Acari (Parasitiformes and Acariformes) From Mexico: Analysis of Their Geographical and Host Distribution in Rodentia (Cricetidae). Issue 6 (14th September 2022) - Herrera-Mares, Angel; Guzmán-Cornejo, Carmen; García-Prieto, Luis; Rebollo-Hernández, Andrea; León-Paniagua, Livia; Del Castillo-Martínez, Laura; Montiel-Parra, Griselda; Ríos-Sais, Gerardo
Abstract: The study of Acari associated with cricetid rodents in Mexico began at the end of the 1930s. Despite efforts to gathering the information, only listings were built, but none of these studies present an analysis of the available data. A search was made through electronic databases; in addition, some not published records contained at Collection of Laboratorio de Acarología, Facultad de Ciencias, Universidad Nacional Autónoma de México were included in the inventory. Combining the literature records and those deposited in the collection, the total number of species of Acari associated with this family of rodents is 165, distributed in two superorders, four orders, 15 families, and 57 genera. Of the 15 families registered, the richest is Trombiculidae (70 nominal species and 75 taxa), followed by Laelapidae (39 and 42, respectively), Ixodidae (13 nominal and 16 taxa), and Leewenhoekiidae (13 nominal and taxa). From the bibliographic searches, a total of 76 papers were recovered with information on the association between Acari and cricetid rodents in Mexico. The main detected approach in the literature was taxonomic (75 works) and one on detection of pathogens. From the 145 known species of cricetids recorded in Mexico, only 72 (distributed in 18 genera) have been studied and found to host Acari. The use of regionalization of Mexico in provinces allowed us to map the records of Acari associated to cricetids in the most natural approximation of their distribution. We recognize and discuss seven factors that favor the scarcity and asymmetry of acarological studies in Mexico. Graphical Abstract: